PENERAPAN METODE ESTAFET WRITING DALAM PEMBELAJARAN MENULIS TEKS CERITA PENDEK PADA SISWA KELAS XI SMA NEGERI 1 KRANGKENG TAHUN PELAJARAN 2023/2024 - Nurjanah; Tobroni; Khoirul Fajri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The author's concern about the low ability of students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year in learning to write short story texts and the limitations of teachers in designing effective learning methods to improve students' skills in writing short story texts is the background to this research. One effort that can be done is by applying the relay writing method in learning to write short story texts. This study aims to: 1) test the effectiveness of the relay writing method in learning to write short story texts for class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year and 2) find out how students' activities in learning to write short story texts by applying the relay writing method to class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year. This study uses an experimental method with a nonequivalent control group design quasi-experimental design (quasi-experimental design) type of nonequivalent control group design. The population of this study was all class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year. The sampling technique used by the researcher in this study was purposive sampling technique, class XI IPS 1 was designated as the control class with 34 students and class XI MIPA 8 as the experimental class with 36 students. Research data were collected through written tests and observation sheets. Based on the results of data processing, the results of the learning process of writing short story texts for class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 academic year experienced an increase between before and after learning with the relay writing method, as evidenced by the average initial test of 72.50 and the final test of 79.31. Based on the results of statistical calculations using the two independent t-test (independent samples test), the t count was 3.842 and the t table was 1.670. So, t count (3.842)> t table (1.670), this indicates that H1 is accepted and H0 is rejected. Thus, it can be stated that the Estafet Writing method is effectively applied in learning to write short story texts for class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year. Based on the analysis of observational data, it is proven that the use of the Estafet Writing method can increase student activeness in the learning process of writing short story texts for class XI students of SMA Negeri 1 Krangkeng in the 2023/2024 Academic Year.